PTFE-based self-lubricating composite coating material and preparation method thereof
By using graphene and alumina in the PTFE coating at the same time and anchoring the alumina through coupling agent, the problem of insufficient wear resistance of the PTFE coating is solved, and the wear resistance and service life are significantly improved.
Patent Information
- Application Number
- CN202411175673.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-17
AI Technical Summary
The wear resistance of PTFE-based self-lubricating composite coating is insufficient, which affects its service life and reliability.
Graphene and alumina are used as fillers at the same time, and alumina is anchored on the graphene through coupling agent to form a uniformly distributed filler to improve the wear reduction and mechanical properties of the coating.
It significantly improves the wear resistance and mechanical properties of PTFE coating, extends the service life, and improves the interface combination between the filler and the matrix through chemical bonds, enhancing the synergistic lubrication effect.
Smart Images

Figure CN119144191A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite coatings, in particular to a PTFE-based self-lubricating composite coating material and a preparation method thereof. Background Art
[0002] Polytetrafluoroethylene (PTFE) based composite coatings play an important role in modern industrial applications, especially in high load, low friction and lubricant-free environments, where their superior performance is particularly prominent. PTFE is widely used in the preparation of self-lubricating composite coatings due to its extremely low friction coefficient, excellent chemical corrosion resistance and thermal stability.
[0003] Although PTFE-based self-lubricating composite coatings have demonstrated excellent performance in many industrial applications, they still face several challenges at the technical level. The inherent low friction coefficient and good chemical corrosion resistance of PTFE materials give them an advantage in the field of self-lubrication, but their mechanical properties are relatively poor, especially their wear resistance is insufficient, which affects the service life and reliability of the overall material. Therefore, it is necessary to modify it to improve the wear resistance of the PTFE coating and extend its service life. Summary of the invention
[0004] In view of this, the present invention provides a PTFE-based self-lubricating composite coating material and a preparation method thereof, which solves the problem of weak interface bonding when alumina and graphene are used as fillers at the same time and poor wear resistance of PTFE, and significantly enhances the wear resistance of the coating while further improving the wear reduction performance of the PTFE coating.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] In one aspect, the present invention discloses a method for preparing a PTFE-based self-lubricating composite coating material, comprising the following steps:
[0007] S1, adding graphene to an organic solvent and dispersing it by ultrasonication to obtain a graphene dispersion;
[0008] S2, mixing the coupling agent with deionized water, adjusting the pH value to 2-4, slowly adding it to the graphene dispersion, stirring and reacting at 50-70°C, and then adding alumina, and obtaining alumina-anchored graphene powder after ultrasonic dispersion, magnetic stirring, vacuum filtration, washing, drying and grinding;
[0009] S3, adding alumina-anchored graphene powder to a mixed solution of polyimide and PTFE, and obtaining a friction-reducing self-lubricating PTFE slurry after ultrasonic dispersion and magnetic stirring;
[0010] S4, coating the anti-friction self-lubricating PTFE mud on the surface of the steel-backed copper powder plate, and then cold rolling, drying and hot pressing to obtain the anti-friction self-lubricating PTFE composite plate.
[0011] As a further solution of the present invention: in step S3, the mass ratio of polyimide, PTFE and water in the mixed solution is 15:(60-65):120.
[0012] As a further solution of the present invention: in step S4, the drying temperature is 140-160° C., and the drying time is 20-30 min.
[0013] As a further solution of the present invention: in step S4, the hot pressing temperature is 350-400°C, the pressure is 25-40MPa, and the holding time is at least 5h.
[0014] As a further solution of the present invention: the mass ratio of graphene, silane coupling agent, aluminum oxide, polyimide and polytetrafluoroethylene is (2-8): (0.5-3): (1-2): 15: (64-65).
[0015] As a further solution of the present invention: the silane coupling agent is aminopropyltriethoxysilane coupling agent.
[0016] As a further solution of the present invention: the particle size of the aluminum oxide is 15-25 nm.
[0017] As a further solution of the present invention: the graphene has a thickness of 0.8 to 1.2 nm and a sheet diameter of 0.5 to 2.0 μm.
[0018] On the other hand, the present invention discloses a PTFE-based self-lubricating composite coating material, which is prepared by the above-mentioned preparation method.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention adds graphene and alumina as fillers to the PTFE matrix at the same time, which can not only give play to the friction reduction and high strength of graphene, but also give play to the wear resistance and high hardness of alumina, thus producing a significant synergistic effect and improving the friction reduction, wear resistance and mechanical properties of the composite coating;
[0021] 2. Anchoring alumina on graphene, the lamellar structure of graphene can promote the uniform distribution of alumina particles in the matrix, reduce agglomeration, and ensure uniform dispersion of fillers;
[0022] 3. Graphene has low surface energy and alumina has high surface energy. The coupling agent used in the present invention plays an important role in interface modification. By forming a chemical bond between the filler and the matrix, the interface bonding between graphene and alumina and between graphene and the PTFE matrix is improved, and the synergistic lubrication effect of alumina and graphene is further exerted. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The SEM image and element distribution results of the alumina-anchored graphene prepared in Example 3. DETAILED DESCRIPTION
[0024] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0026] The specific information of the raw materials used in the following examples and comparative examples is as follows:
[0027] γ-aminopropyltriethoxysilane coupling agent, brand KH550, manufacturer: Nanjing Youpu Chemical Co., Ltd.;
[0028] Alumina, particle size is 20nm, brand name α-Al2O3, manufacturer Zhengzhou Xinli Wear Resistant Materials Co., Ltd.;
[0029] Graphene, brand name multilayer graphene, manufacturer Nanjing Xianfeng Nanomaterial Technology Co., Ltd.;
[0030] Polyimide, manufacturer Changzhou Yaan New Materials Co., Ltd.;
[0031] Polytetrafluoroethylene, manufacturer Yixin Plastic Materials Co., Ltd.;
[0032] All materials are commercially available conventional products.
[0033] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.
[0034] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0035] The following Table 1 shows the proportions of the components in each embodiment.
[0036] Table 1
[0037]
[0038]
[0039] Example 1
[0040] (1) Ingredients
[0041] Weigh each component according to Table 1 for later use.
[0042] (2) Preparation of alumina-anchored graphene fillers
[0043] Add 8g of graphene to 100ml of anhydrous ethanol solution, ultrasonically disperse for 20min, and magnetically stir for 1h to obtain a graphene dispersion. Add 0.5g of γ-aminopropyltriethoxysilane coupling agent and 50ml of deionized water to another beaker, adjust the pH value to 3, stir and hydrolyze for 30min, then slowly add to the graphene dispersion, and magnetically stir at 60℃ for 4h. Add 1g of alumina to the solution, ultrasonically disperse for 20min, and magnetically stir for 2h. Repeat the vacuum filtration and washing three times, dry at 80℃ for 12h, and grind to prepare alumina-anchored graphene powder for storage.
[0044] (3) Mixed powder
[0045] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Slowly add the prepared alumina-anchored graphene powder into the solution, stir while pouring, ultrasonically disperse for 20 minutes, magnetically stir for 2 hours, and mix evenly to obtain a friction-reducing self-lubricating PTFE-based mud-like composite material.
[0046] (4) Cold rolling
[0047] The PTFE-based mud-like composite coating is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0048] (5) Drying
[0049] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0050] (6) Hot pressing
[0051] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based self-lubricating composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0052] Example 2
[0053] (1) Ingredients
[0054] Weigh each component according to Table 1 for later use.
[0055] (2) Preparation of alumina-anchored graphene fillers
[0056] Add 2g of graphene to 100ml of anhydrous ethanol solution, ultrasonically disperse for 20min, and magnetically stir for 1h to obtain a graphene dispersion. Add 3g of γ-aminopropyltriethoxysilane coupling agent and 50ml of deionized water to another beaker, adjust the pH value to 3, stir and hydrolyze for 30min, then slowly add to the graphene dispersion, and magnetically stir at 60℃ for 4h. Add 2g of alumina to the solution, ultrasonically disperse for 20min, and magnetically stir for 2h. Repeat the vacuum filtration and washing three times, dry at 80℃ for 12h, and grind to prepare alumina-anchored graphene powder for storage.
[0057] (3) Mixed powder
[0058] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Slowly add the prepared alumina-anchored graphene powder into the solution, stir while pouring, ultrasonically disperse for 20 minutes, magnetically stir for 2 hours, and mix evenly to obtain a friction-reducing self-lubricating PTFE-based mud-like composite material.
[0059] (4) Cold rolling
[0060] The PTFE-based mud-like composite coating is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0061] (5) Drying
[0062] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0063] (6) Hot pressing
[0064] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based self-lubricating composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0065] Example 3
[0066] (1) Ingredients
[0067] Weigh each component according to Table 1 for later use.
[0068] (2) Preparation of alumina-anchored graphene fillers
[0069] Add 4g of graphene to 100ml of anhydrous ethanol solution, ultrasonically disperse for 20min, and magnetically stir for 1h to obtain a graphene dispersion. Add 2g of γ-aminopropyltriethoxysilane coupling agent and 50ml of deionized water to another beaker, adjust the pH value to 3, stir and hydrolyze for 30min, then slowly add to the graphene dispersion, and magnetically stir at 60℃ for 4h. Add 1.5g of alumina to the solution, ultrasonically disperse for 20min, and magnetically stir for 2h. Repeat the vacuum filtration and washing three times, dry at 80℃ for 12h, and grind to prepare alumina-anchored graphene powder for later use.
[0070] (3) Mixed powder
[0071] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Slowly add the prepared alumina-anchored graphene powder into the solution, stir while pouring, ultrasonically disperse for 20 minutes, magnetically stir for 2 hours, and mix evenly to obtain a friction-reducing self-lubricating PTFE-based mud-like composite material.
[0072] (4) Cold rolling
[0073] The PTFE-based mud-like composite coating is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0074] (5) Drying
[0075] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0076] (6) Hot pressing
[0077] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based self-lubricating composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0078] Example 4
[0079] (1) Ingredients
[0080] Weigh each component according to Table 1 for later use.
[0081] (2) Preparation of alumina-anchored graphene fillers
[0082] Add 8g of graphene to 100ml of anhydrous ethanol solution, ultrasonically disperse for 20min, and magnetically stir for 1h to obtain a graphene dispersion. Add 3g of γ-aminopropyltriethoxysilane coupling agent and 50ml of deionized water to another beaker, adjust the pH value to 3, stir and hydrolyze for 30min, then slowly add to the graphene dispersion, and magnetically stir at 60℃ for 4h. Add 2g of alumina to the solution, ultrasonically disperse for 20min, and magnetically stir for 2h. Repeat the vacuum filtration and washing three times, dry at 80℃ for 12h, and grind to prepare alumina-anchored graphene powder for storage.
[0083] (3) Mixed powder
[0084] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Slowly add the prepared alumina-anchored graphene powder into the solution, stir while pouring, ultrasonically disperse for 20 minutes, magnetically stir for 2 hours, and mix evenly to obtain a friction-reducing self-lubricating PTFE-based mud-like composite material.
[0085] (4) Cold rolling
[0086] The PTFE-based mud-like composite coating is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0087] (5) Drying
[0088] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0089] (6) Hot pressing
[0090] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based self-lubricating composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0091] Example 5
[0092] (1) Ingredients
[0093] Weigh each component according to Table 1 for later use.
[0094] (2) Preparation of alumina-anchored graphene fillers
[0095] Add 2g of graphene to 100ml of anhydrous ethanol solution, ultrasonically disperse for 20min, and magnetically stir for 1h to obtain a graphene dispersion. Add 0.5g of γ-aminopropyltriethoxysilane coupling agent and 50ml of deionized water to another beaker, adjust the pH value to 3, stir and hydrolyze for 30min, then slowly add to the graphene dispersion, and magnetically stir at 60℃ for 4h. Add 1g of alumina to the solution, ultrasonically disperse for 20min, and magnetically stir for 2h. Repeat the vacuum filtration and washing three times, dry at 80℃ for 12h, and grind to prepare alumina-anchored graphene powder for storage.
[0096] (3) Mixed powder
[0097] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Slowly add the prepared alumina-anchored graphene powder into the solution, stir while pouring, ultrasonically disperse for 20 minutes, magnetically stir for 2 hours, and mix evenly to obtain a friction-reducing self-lubricating PTFE-based mud-like composite material.
[0098] (4) Cold rolling
[0099] The PTFE-based mud-like composite coating is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0100] (5) Drying
[0101] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0102] (6) Hot pressing
[0103] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based self-lubricating composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0104] Comparative Example 1
[0105] (1) Ingredients
[0106] Weigh each component according to Table 1 for later use.
[0107] (2) Preparation of alumina-anchored graphene fillers
[0108] Add 4g of graphene to 100ml of anhydrous ethanol solution, ultrasonically disperse for 20min, and magnetically stir for 1h to obtain a graphene dispersion. Add 50ml of deionized water to another beaker, then slowly add it to the graphene dispersion, and magnetically stir at 60℃ for 4h. Add 1.5g of alumina to the solution, ultrasonically disperse for 20min, and magnetically stir for 2h. Repeat the vacuum filtration and washing three times, dry at 80℃ for 12h, and store the ground powder for later use.
[0109] (3) Mixed powder
[0110] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Slowly add the powder obtained in step (2) into the solution, stir while pouring, ultrasonically disperse for 20 minutes, and magnetically stir for 2 hours to obtain a mud-like composite material.
[0111] (4) Cold rolling
[0112] The mud-like composite coating is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0113] (5) Drying
[0114] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0115] (6) Hot pressing
[0116] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0117] Comparative Example 2
[0118] (1) Mixed powder
[0119] Prepare 75g of 20% polyimide solution (20%*75=15g) and 108g of 60% PTFE emulsion (60%*108=64.8g). Mix the two solutions and stir them evenly to obtain a mixed solution. Pour 3g of PTFE powder into the mixed solution, stir it in a high-speed mixer for 1h, and mix evenly to obtain a friction-reducing self-lubricating PTFE-based mud-like composite material.
[0120] (2) Cold rolling
[0121] The PTFE mud material is placed on the surface of the steel-backed copper powder plate, and the plate is rolled using a rolling mill to spread the mud evenly on the surface of the plate.
[0122] (3) Drying
[0123] The cold-rolled sheet was dried at an oven temperature of 150°C for 20 min.
[0124] (4) Hot pressing
[0125] Place the cold-rolled sheet in the center of the mold. Set the hot press temperature to 370°C, the pressure to 30 MPa, and the holding time to 6 hours. A PTFE-based self-lubricating composite sheet with a total thickness of 2 mm and a PTFE layer thickness of 0.2 mm is obtained.
[0126] The PTFE-based self-lubricating materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were subjected to surface hardness testing and friction and wear tests. According to the ASTM-D224 standard, a Shore hardness tester (type D) was used to measure the hardness of a 25 mm (length) 20 mm (width) 6 mm (thickness) sample. Depth measurements were performed at 5 locations on each sample, and the average hardness value was calculated. The indentation load for each measurement was 22.5 N, and the holding time was 15 s. The variation of the hardness value was within 10% of the average value.
[0127] The friction and wear experiment used a HDM-200 end face friction and wear tester to test the tribological properties of each group of coating samples. The test device adopts the end face to end face contact form, and the material of the dual part is 42CrMo. Before each experiment, the end face of the dual part is polished with 800 mesh sandpaper to ensure that its surface roughness (Ra) is 0.2-0.4um. In order to ensure the cleanliness of the material surface, acetone and anhydrous ethanol are ultrasonically cleaned for 15 minutes in turn before the test, and then the dual part and the test sample are dried with hot air. Five samples were prepared for each embodiment and comparative example, and each test lasted 60 minutes. The friction coefficient u of the experimental results was averaged, and three significant figures were retained according to rounding.
[0128] Table 2 Performance test results of PTFE-based self-lubricating materials prepared in various embodiments and comparative examples
[0129] project hardness Friction coefficient Wear rate Example 1 88 0.162 <![CDATA[6.9×10-5mm 3 / Nm]]> Example 2 92 0.159 <![CDATA[7.1×10-5mm 3 / Nm]]> Example 3 89 0.147 <![CDATA[5.8×10-5mm 3 / Nm]]> Example 4 97 0.160 <![CDATA[6.4×10-5mm 3 / Nm]]> Example 5 84 0.163 <![CDATA[7.6×10-5mm 3 / Nm]]> Comparative Example 1 79 0.194 <![CDATA[6.9×10-4mm 3 / Nm]]> Comparative Example 2 71 0.201 <![CDATA[4.8×10-3mm 3 / Nm]]>
[0130] From Table 2, the hardness of the PTFE-based self-lubricating composite coating prepared in each embodiment is higher than that of the comparative example. The friction coefficient and wear rate are lower than those of the comparative example, and the wear rate is different from that of the comparative example in magnitude, which further proves that the material prepared in the embodiment has excellent friction reduction and wear resistance. Figure 1 It can be seen that alumina is evenly anchored on graphene, and alumina and graphene are tightly combined.
[0131] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0132] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A method for preparing a PTFE-based self-lubricating composite coating material, characterized in that: The following steps are involved: S1, adding graphene to an organic solvent and dispersing it by ultrasonication to obtain a graphene dispersion; S2, mixing the coupling agent with deionized water, adjusting the pH value to 2-4, slowly adding it to the graphene dispersion, stirring and reacting at 50-70°C, and then adding alumina, and obtaining alumina-anchored graphene powder after ultrasonic dispersion, magnetic stirring, vacuum filtration, washing, drying and grinding; S3, adding alumina-anchored graphene powder to a mixed solution of polyimide and PTFE, and obtaining a friction-reducing self-lubricating PTFE slurry after ultrasonic dispersion and magnetic stirring; S4, coating the anti-friction self-lubricating PTFE mud on the surface of the steel-backed copper powder plate, and then cold rolling, drying and hot pressing to obtain the anti-friction self-lubricating PTFE composite plate.
2. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of polyimide, PTFE and water in the mixed solution is 15:(60-65):
120.
3. The preparation method according to claim 1, characterized in that: In step S4, the drying temperature is 140-160° C., and the drying time is 20-30 min.
4. The preparation method according to claim 1, characterized in that: In step S4, the hot pressing temperature is 350-400° C., the pressure is 25-40 MPa, and the holding time is at least 5 hours.
5. The preparation method according to claim 1, characterized in that: The mass ratio of graphene, silane coupling agent, alumina, polyimide and polytetrafluoroethylene is (2-8): (0.5-3): (1-2): 15: (64-65).
6. The preparation method according to claim 1, characterized in that: The silane coupling agent is aminopropyltriethoxysilane coupling agent.
7. The preparation method according to claim 1, characterized in that: The particle size of the aluminum oxide is 15-25 nm.
8. The preparation method according to claim 1, characterized in that: The graphene has a thickness of 0.8 to 1.2 nm and a sheet diameter of 0.5 to 2.0 μm.
9. A PTFE-based self-lubricating composite coating material, prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Alumina-based ceramic tool material containing graphene coated alumina composite powder and preparation method of alumina-based ceramic tool material
CN107555965A
Polyformaldehyde composite material and preparation method thereof
CN109181208A
Preparation method of modified reduced graphene oxide / nano-alumina composite material modified PI wear-resistant film
CN113549230A
Universal type metal-plastic three-layer composite material suitable for various lubricating conditions and preparation method of universal type metal-plastic three-layer composite material
CN116874958A
Antifriction and wear-resistant composite material as well as preparation method and application thereof
CN117430902A
